Investigation and analysis of digital demand for children's books - Zhang, Wenting; Liu, Qian (Nurture, 2023)
Purpose: This study aims to examine and assess the requirements of Chinese children in relation to digital reading. It also seeks to explore the challenges that arise in the production of digital reading materials for children while proposing principles for their future development. Design/Methodology/Approach: A sample of 600 participants was selected from mainland China for the purpose of this study. A total of 483 valid surveys were gathered and utilized to examine the elements that influence the effectiveness of digital reading in children. Findings: The results of this study demonstrate a positive association between the level of digitalization in children's books and children's digital reading proficiency. These findings show that a greater degree of digitization is linked to a more advantageous impact on digital reading skills. Conclusion: To enhance the efficacy of digital reading among children, it is imperative to strengthen the level of digitization in the design of children's books while concurrently fostering children's willingness towards digital books. In digitizing children's books, it is essential to enhance the usability of goods, simplify operation processes, and reduce the design of interfaces to foster a sense of enjoyment and satisfaction among young readers. Research Limitations: The target user group for this study is children between the ages of 3-6. Due to the young age of the study subjects, they cannot fill out the questionnaire independently, and the questionnaire is filled out with the assistance of their parents, which cannot fully reflect the subjective intention and actual situation of the study subjects.